ADWE-03 Cryoablation for the treatment of refractory oesophageal neoplasia after unsuccessful first line endoscopic eradication therapy. (8th June 2018) - Alzoubaidi, Durayd; Magee, Cormac; Everson, Martin; Graham, David; Lovat, Laurence; Haidry, Rehan
Abstract : Introduction: Endoscopic eradication therapy EET with endoscopic mucosal resection EMR for visible lesions followed by Radiofrequency ablation RFA for flat Barrett's oesophagus BE is the gold standard treatment for patients with BE related neoplasia. In a minority of patients EET is unsuccessful and alternative therapies are desirable. Cryoablation with the Cryoballoon device (C2 therapeutics) is a novel ablative therapy that uses cycles of freezing and thawing to induce cell death by intra and extracellular ice formation, vascular injury, and apoptosis. Aim: Single centre study to evaluate the feasibility of the focal cryoablation device for the treatment of areas of refractory oesophageal neoplasia in patients who had undergone first line EET. Endpoints: CR-D and CR-IM at 3 month follow up. The rate of stenosis and adverse events were also studied. Method: A total of 16 cases (11 M, 5 F) have been treated by a single experienced endoscopist. Baseline histology included 7 Low Grade Dysplasia LGD, 5 High Grade Dysplasia HGD, 2 Intramucosal cancer (IMC) and 2 patients with Early Squamous Cell Neoplasia ESCN. All patients had residual neoplasia after sequential first line EET. The median length of dysplastic BE treated was 3 cm (Range: 1–10) in 14 cases and 3 cm of a visible lugols-voiding-mucosa in 2 patients with ESCN. An average of 10 ablations applied per patient (range 2–24). Each selected area of visible dysplasia received 10 s of ablation. Only 1 session of cryoablation per patient. Endoscopy and rebiopsy from the treated sites were taken at 3 months post ablation to assess for end points. Results: CR-D achieved in 75% (12/16) of all patients at first follow up. In those with BE the CR-D was 79% (11/14) and CR-IM 36% (5/14). 1 of the patients with ESCN did not respond to Cryoablation and was referred for radiotherapy. There was progression from LGD to HGD in 1 BE case that was treated with EMR. Technical difficulty due to challenging anatomy was noted in 1 case with tortuous and dilated oesophagus. There were no device malfunction or adverse events. Stenosis was noted in 6% of cases. Conclusion: In this single centre feasibility cohort study, Cryoablation with the cryoballoon device appears to be a viable strategy in patients with refractory neoplasia after sequential first line EET. It is well tolerated and partially successful in obtaining CR-D and CR-IM in 'treatment-refractory' patients with BE dysplasia. Further trials of dosimetry, efficacy and safety in 'treatment-naïve' patients with randomised controlled trials is recommended and are underway.